2012
DOI: 10.1089/scd.2011.0422
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor DLX3 Regulates the Osteogenic Differentiation of Human Dental Follicle Precursor Cells

Abstract: The transcription factor DLX3 plays a decisive role in bone development of vertebrates. In neural-crest derived stem cells from the dental follicle (DFCs), DLX3 is differentially expressed during osteogenic differentiation, while other osteogenic transcription factors such as DLX5 or RUNX2 are not highly induced. DLX3 has therefore a decisive role in the differentiation of DFCs, but its actual biological effects and regulation are unknown. This study investigated the DLX3-regulated processes in DFCs. After DLX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…Dlx3 is a member of the distalless homeobox family that interacts with transcription factors specific to mineralized tissue to regulate craniofacial and postnatal skeletal development (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Our results indicate that there is a cellular requirement for miR-665 to fine-tune the expression of Dlx3 within physiologic limits for maturation of progenitors to odontoblasts.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Dlx3 is a member of the distalless homeobox family that interacts with transcription factors specific to mineralized tissue to regulate craniofacial and postnatal skeletal development (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Our results indicate that there is a cellular requirement for miR-665 to fine-tune the expression of Dlx3 within physiologic limits for maturation of progenitors to odontoblasts.…”
Section: Discussionmentioning
confidence: 78%
“…Studies from several research groups have revealed that homeodomain gene Dlx3 (Online Mendelian Inheritance in Man [OMIM] entry 600525) is a highly critical regulator of craniofacial and postnatal skeletal development (28)(29)(30)(31)(32)(33)(34). Mutations in DLX3 in humans have been associated with tricho-dento-osseous syndrome (TDO; OMIM 190320) and amelogenesis imperfecta with taurodontism (AIHHT; OMIM 104510), both of which are conditions characterized by abnormalities in tooth formation (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…[52,53] Dlx3 collaborates with transcription factors unique to mineralized tissue to regulate craniofacial and postnatal skeletal development. [54][55][56] Dlx3 stimulates dentinogenesis. The posttranscriptional regulation of Dlx3 by miR-665 controlled by BMP2 and RUNX2, implies an combined network of signaling and transcription factors that coordinate the stagespecific events of odontoblast differentiation.…”
Section: Dentinogenesismentioning
confidence: 99%
“…Using microarray technology, the authors showed that overexpression of DLX3 in DFSCs leads to upregulation of 73 genes ( e.g ., IL8, CXCL10, CXCL11, MMP1, BMP2, NR4A2, HES1 and ATF3) and downregulation of 55 genes ( e.g ., COL3A1, ELN, OMD and PLXNC1). DLX3 regulates osteogenic differentiation and mineralization of DFSCs through BMP2-dependent pathway and feedback control [ 60 ].…”
Section: Genetic Modifi Cation For Modulation Of Cell Phenotype and Omentioning
confidence: 99%